A carbon nanotubes-pectin composite for electrochemical determination of copper in aviation biokerosene by anodic stripping voltammetry - Primo, Carolina Martins [UNESP] (2021)
This work reports the development of a simple, sensitive and low-cost electroanalytical method for copper determination in aviation biokerosene using an electrode modified with a composite made up of multi-walled carbon nanotubes and pectin. The proposed electrode was characterized by cyclic voltammetry, electrochemical impedance spectroscopy, scanning electron microscopy and RAMAN spectroscopy. Using square wave anodic stripping voltammetry, the method developed presented a linear working range of 1.0 × 10−8 to 1.0 × 10−6 mol L−1. The limits of detection and quantification obtained for this methodology were 9.0 × 10−9 mol L−1 and 3.0 × 10−8 mol L−1, respectively. The proposed electrode experienced no interference from matrix effect when applied for copper determination in aviation biokerosene. The results obtained were validated by recovery assays and compared with the flame atomic absorption spectroscopy method. Essentially, these results indicate that the proposed electrode has good accuracy for copper determination and can be successfully applied for the monitoring of copper in aviation biokerosene.